N2O and CH4 emissions, and NO3- leaching on a crop-yield basis from a subtropical rain-fed wheat-maize rotation in response to different types of nitrogen fertilizer - Zhou, M.; Zhu, B.; Bruggemann, N.; Bergmann, J.; Wang, Y.; Butterbach-Bahl, Klaus (Springer, 2014)
Guaranteeing high crop yields while reducing environmental impacts of nitrogen fertilizer use due to associated losses of N2O emissions and nitrate (NO3 −) leaching is a key challenge in the context of sustainable intensification of crop production. However, few field data sets are available that explore the effect of different forms of N management on yields as well as on N losses in the form of N2O or NO3 −. Here we report on a large-scale field lysimeter (8 × 4 m2) experiment, which was designed to determine soil CH4 and N2O emissions, NO3 − leaching losses and crop yields from a subtropical rain-fed wheat–maize rotation in the Sichuan Basin, one of the most intensively used agricultural regions in China. One control and three different fertilizer treatments with the same total rate of N application (280 kg N ha−1 y−1) were included: NF: control (no fertilizer); NPK: synthetic N fertilizer; OMNPK: synthetic N fertilizer plus pig manure; RSDNPK: synthetic N fertilizer plus crop residues. As compared to the standard NPK treatment, annual NO3 − leaching losses for OMNPK and RSDNPK treatments were decreased by 36 and 22%, respectively (P < 0.05). Similarly, crop yield-scaled NO3 − leaching for NPK treatment was higher than those for either OMNPK or RSDNPK treatments (P < 0.05). Direct N2O emissions for RSDNPK treatment were decreased as compared with NPK and OMNPK treatments (P < 0.05). Furthermore, the yield-scaled GWP (global warming potential) was lower for the treatments where either pig manure or crop residues were incorporated as compared to the standard NPK treatment (P < 0.05). Our study indicates that it is possible to reduce the negative environmental impact of NO3 − leaching and N2O emissions without compromising crop productivity. Yield-scaled NO3 − leaching, similar to the yield-scaled GWP, represents another valuable-integrated metric to address the dual goals of reducing nitrogen pollution and maintaining crop grain yield for a given agricultural system.